Quality and Consumers Acceptence of Shredded Rough Flathead Fish (Grammoplites scaber) - Khoiriah; Fikri, Muhammad Zakiyul; Yusfiani, Marnida (Talenta Publisher, 2022)
Shredded fish is a type of processed fish that is seasoned, processed by boiling and frying. The resulting product has a soft shape, good taste, special smell, and has a relatively long shelf life. This study aims to find out the level of acceptance of panelists through organoleptic test and find out the quality of shredded fish products from Rough flathead (Grammoplites Scaber) through proximate tests. the method used in this study consists of three stages. the first stage is the stage of making shredded fish. The second stage is organoleptic testing. next is the third stage of proximate testing. Organoleptic test results of shredded fish from Rough flathead (Grammoplites scaber) is 9.00 appearance, 8.66 smell, 8.48 taste, and 8.48 texture. The proximate test results of water content values of 12.20%, ash content of 6.93%, fat content of 19.01%, protein content of 22.93%, and carbohydrate content of 9.06%.